Analisis Wacana “Pariwisata Muslim Friedly” Dalam Perspektif Politik Ekonomi Islam - Ainur Ropik; Afif Musthofa Kawwami (T JDP (JURNAL DINAMIKA PEMERINTAHAN), 2022)
This study analyzes the discourse of "Muslim friendly tourism" in the perspective of Islamic economic politics. The research method used in this study is a qualitative method using a critical discourse analysis approach. In addition, this study also uses the concept of 3 (three) paradigms in the perspective of Islamic economic politics as a knife of analysis, including; integralistic paradigm, secularistic paradigm, and symbiotic paradigm. This study concludes that the discourse of "Muslim Friendly Tourism" has led to conflicts in several regions in Indonesia. One of them is in North Sumatra. Basically, this happens, because the government as the policy maker and implementer cannot take a persuasive approach to the community. In addition, the discourse of "Muslim Friendly Tourism" is also more directed to the Symbiotic paradigm, because it emphasizes substance rather than a legal and formal state form. Due to its substantial nature (by emphasizing the values ​​of justice, equality, deliberation, and participation, which do not conflict with Islamic principles), this tendency has the potential to act as an approach that can connect Islam with the modern political and economic system, in where the state (nation state) is one of the main elements.